2022
DOI: 10.3389/fmolb.2022.986704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a plant cyclotide on conformational dynamics and destabilization of β-amyloid fibrils through molecular dynamics simulations

Abstract: Aggregation of β-amyloid (Aβ) peptide is one of the hallmarks of Alzheimer’s disease (AD) which results in chronic and progressive neurodegeneration of the brain. A recent study by our group have shown the ability of cyclic disulfide-rich peptides (“cyclotides”) isolated from a medicinal plant, Clitoria ternatea, to inhibit the aggregation of Aβ peptides and reduce oxidative stress caused by reactive oxygen species using in vivo models of transgenic Caenorhabditis elegans. In the present study, through extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…139 The peptide was subsequently docked onto 3D structures of Ab 42 fibrils and subjected to molecular dynamics simulations. 140 The results explained experimental observations to reveal that the Cter-M cyclotide from C. ternatea (GLPTCGETCTLGTCYVPDCSCSW-PICMKN) binds the Ab 42 fibril via hydrogen bonding, hydrophobic, electrostatic and p-p interactions, thereby inhibiting aggregation. 140 Particularly, the peptide disrupts intermolecular hydrogen bonds and salt bridges in the Ab 42 fibril, which are crucial for its structural integrity.…”
Section: Molecular Dynamics Simulations In Peptide Designmentioning
confidence: 56%
See 1 more Smart Citation
“…139 The peptide was subsequently docked onto 3D structures of Ab 42 fibrils and subjected to molecular dynamics simulations. 140 The results explained experimental observations to reveal that the Cter-M cyclotide from C. ternatea (GLPTCGETCTLGTCYVPDCSCSW-PICMKN) binds the Ab 42 fibril via hydrogen bonding, hydrophobic, electrostatic and p-p interactions, thereby inhibiting aggregation. 140 Particularly, the peptide disrupts intermolecular hydrogen bonds and salt bridges in the Ab 42 fibril, which are crucial for its structural integrity.…”
Section: Molecular Dynamics Simulations In Peptide Designmentioning
confidence: 56%
“…140 The results explained experimental observations to reveal that the Cter-M cyclotide from C. ternatea (GLPTCGETCTLGTCYVPDCSCSW-PICMKN) binds the Ab 42 fibril via hydrogen bonding, hydrophobic, electrostatic and p-p interactions, thereby inhibiting aggregation. 140 Particularly, the peptide disrupts intermolecular hydrogen bonds and salt bridges in the Ab 42 fibril, which are crucial for its structural integrity. The effects occur within the first 50 ns of the simulations with disruptions in the fibril secondary structure at residues 2-7 and 38-41, resulting in the loss of extended b-sheet conformations.…”
Section: Molecular Dynamics Simulations In Peptide Designmentioning
confidence: 56%
“…The documented inhibition of prolyl oligopeptidase by knottin-like cyclotides [ 13 , 130 ] should trigger scientific investigation of the potential of knottin-like peptides, to inhibit the enzymes involved in a cascade of reactions leading to the extracellular plaques of beta-amyloid peptide (Aβ) deposits in the brain observed in Alzheimer’s disease [ 131 ]. As a first step, Kalmankar and colleagues [ 132 ] showed that cyclotides from Clitoria ternatea can inhibit the aggregation of amyloid β peptide (Aβ). This computational study showed that cyclotides can prevent Alzheimer’s progression by binding to peptide structures and inhibiting their aggregation.…”
Section: Limitations To the Pharmaceutical Applications Of Knottin-ri...mentioning
confidence: 99%